Managing gender diversity and barriers to inclusion: lived experiences of women employees in a South African coal mining company - Baker, Sabelo M.; Ngonyama-Ndou, Thulile L.; Skosana, Thulani B. (Frontiers in Sociology, 2025)
IntroductionIn the context of growing global commitments to workplace diversity and inclusion, South Africa's mining sector remains a site of persistent gender inequality. Despite policy frameworks informed by liberal feminist ideals that emphasize equal rights, representation, and opportunity, women continue to experience structural and cultural barriers that hinder their advancement. This study addresses the urgent need for context-sensitive, experience-based approaches to understanding gender inequality in male-dominated industries.MethodsA qualitative, interpretive phenomenological approach was employed to explore the lived experiences of 12 purposively selected women working in various departments at a coal mining company in Mpumalanga. Semi-structured interviews were conducted to capture how these women navigate hostile workplace environments characterized by sexual harassment, gender stereotyping, unsafe working conditions, and limited access to leadership pathways. Thematic analysis was then applied using Braun and Clarke's six-step framework to identify and interpret patterns across data.ResultsThe findings revealed persistent structural and cultural barriers that undermine formal diversity initiatives. Participants' narratives emphasized issues of limited career advancement, biased recruitment practices, exclusionary workplace cultures, safety risks, and difficulties balancing work and family responsibilities. While liberal feminist-informed policies such as the Employment Equity Act and Women in Mining initiatives have formalized inclusion, entrenched patriarchal norms often render such reforms symbolic rather than substantive.DiscussionThese findings highlight the limitations of surface-level reforms and underscore the need for deeper institutional change. Meaningful gender diversity can enhance collaboration, innovation, and workplace morale, but these benefits remain unrealised without stronger policy enforcement, inclusive organizational cultures, mentorship, gender-sensitive recruitment, safe reporting mechanisms, and targeted support for women's professional development. This research provides practical guidance for re-evaluating current diversity strategies and calls for a shift from symbolic inclusion to structural transformation within South Africa's mining industry.